Seismic Structure-Soil-Structure Interaction Between a Pair of Cross-Laminated Timber Buildings Under Seismic Loads - Saavedra-Flores, E; Torres-Olivares, S (Springer Science and Business Media Deutschland GmbH, 2024)
Frequently, buildings in urban areas are designed by considering the response of structures as stand-alone i.e., a single structure, with no neighbouring structures. Nevertheless, the existence of a high density of buildings in large metropolitan areas inevitably results in the likelihood of seismic interaction of adjacent buildings through the underlying soil. This problem is better known as Structure-Soil-Structure Interaction (SSSI), and this interaction can either increase or decrease the seismic response of a structure, and its relevance was highlighted in early studies (Lee and Wesley in Nucl Eng Des 24:374–387, [1]; Kobori et al. Dynamical cross-interaction between two foundation, [2]; Wong and Luco in Soil Dyn Earthq Eng 5:149–158, [3]; Triantafyllidis and Prange in Soil Dyn Earthq Eng 7:40–52, [4]). In this research, we explore the influence of Structure-Soil-Structure Interaction (SSSI) between a pair of cross-laminated timber (CLT) buildings under seismic excitation. A complete 3-dimensional high-order model of the soil and buildings is performed. The finite element method is used for the numerical simulations in ANSYS. The interaction effects are investigated for different heights of the buildings and soil properties. Results suggest that the SSSI can affect displacement, inter-story drift and accelerations. The impact of the SSSI effects is more relevant for loose soil. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.